Ku phamela (servir) alimentos nas cerimônias é hierarquizar e violentar: uma perspectiva sobre direitos humanos e Estado em Maputo, Moçambique - Bila, Josué Julião (Universidade Federal de São Carlos, 2025)
This thesis examines how and why people serve themselves and are served food at marriage ceremonies in Maputo. I observed the way of ku phamela (serving) in the complex world of those celebrations and even in families, where to serve and be served is to fall into a category, sometimes of “person”, sometimes of “individual”. Observing the categorizations of people and individuals led me to understand the problems related to Mozambique's social structure, where hierarchies, privileges and violence are a symbolic weapon for the (de)qualification of social classes and positions. Perhaps this is the reason why in our state a dhla axurha (eats greedily) whoever is hierarchically superior and whoever has networks of intermediaries, in bureaucratic and political environments. Furthermore, when the Mozambican party-state imposed itself in 1975, even though it embodied the Marxist-Leninist ideology, it was, in practice, swallowed up by the mouth of social history, leaving it to reproduce, homologate and reinforce hierarchies, privileges and violence through its governmental and security apparatuses.
Ku phamela (serving) food at ceremonies is hierarchical and violent: a perspective on human rights and the state in Maputo, Mozambique
Keywords: Ku phamela; Alimentos; Hierarquias; Cerimônias matrimoniais; Direitos humanos; Moçambique; Food; Hierarchies; Marriage ceremonies; Human rights; Mozambique; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; 10. Redução das Desigualdades